2012
DOI: 10.1371/journal.pone.0030303
|View full text |Cite
|
Sign up to set email alerts
|

P120-Catenin Isoforms 1 and 3 Regulate Proliferation and Cell Cycle of Lung Cancer Cells via β-Catenin and Kaiso Respectively

Abstract: BackgroundThe different mechanisms involved in p120-catenin (p120ctn) isoforms' 1/3 regulation of cell cycle progression are still not elucidated to date.Methods and FindingsWe found that both cyclin D1 and cyclin E could be effectively restored by restitution of p120ctn-1A or p120ctn-3A in p120ctn depleted lung cancer cells. When the expression of cyclin D1 was blocked by co-transfection with siRNA-cyclin D1 in p120ctn depleted cells restoring p120ctn-1A or 3A, the expression of cyclin E was slightly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 20 publications
(27 reference statements)
4
36
2
Order By: Relevance
“…Our previous study demonstrated that Kaiso binds to p120ctn in lung cancer cells, and that p120ctn 3 is likely to be the major isoform [24], [25], [26]. However, we did not confirm that p120ctn isoform 1A combines with Kaiso.…”
Section: Discussioncontrasting
confidence: 77%
“…Our previous study demonstrated that Kaiso binds to p120ctn in lung cancer cells, and that p120ctn 3 is likely to be the major isoform [24], [25], [26]. However, we did not confirm that p120ctn isoform 1A combines with Kaiso.…”
Section: Discussioncontrasting
confidence: 77%
“…Surprisingly, Ki67 expression was decreased in Line A mice and Ki67 positive cells were localized more apical to the normal crypt/villus boundary (Figure 6A). We next evaluated the expression of the Kaiso target gene cyclin D1 [4], [21] that has been shown to drive proliferation in the intestinal epithelium and is frequently overexpressed in colon cancer [35]. Similar to Ki67, Cyclin D1 expression was also decreased in Line A Kaiso Tg/+ mice but surprisingly the apparent decreased numbers of Cyclin D1 positive (+) cells in Kaiso Tg/+ intestines was not statistically significant (Figure 6B, C).…”
Section: Resultsmentioning
confidence: 99%
“…Since its discovery as a binding partner for the Src kinase substrate and cell adhesion protein p120 ctn , mounting evidence suggests that the POZ-ZF transcription factor Kaiso functions in vertebrate development and tumorigenesis [1], [2], [3], [4], [5], [6], [7], [8]. To date however, Kaiso’s role in these processes in mammalian systems remains unclear, and much controversy surrounds several aspects of Kaiso’s function; this includes the mechanism by which it binds DNA [9], [10], [11], [12], [13], [14], [15], [16], [17] and its function in regulating the canonical Wnt signalling pathway that plays a key role in vertebrate development and tumorigenesis [8], [11], [14], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although this limited number does not indicate larger roles for Kaiso in conjunction with p120 catenin, surprising findings have arisen. In particular, the control regions of a number of mammalian or X. laevis Kaiso target genes (for example, those encoding matrilysin, cyclin D1, WNT11 and Siamois) are regulated not only by Kaiso 45,7985 but also by β-catenin and TCF 86,87,88 . Indeed, although different underlying mechanisms have been proposed 73 , the TCF and Kaiso repressors biochemically associate, their derepression is coordinated at gene control regions and their functional interrelationship has been shown in vivo 45,79 .…”
Section: Nuclear Roles Of Kaiso and P120 Cateninmentioning
confidence: 99%